The Role of Acu-TENS in Hemodynamic Recovery after Open-Heart Surgery. (20th March 2011) - Ng, Maggie C. S.; Jones, Alice Y. M.; Cheng, L. C.
Abstract : Increased heart rate (HR) and reduced blood pressure (BP) are common consequences of cardiac surgery. This study investigated the effect of transcutaneous electrical nervous stimulation applied over acupuncture points (Acu-TENS) on HR, BP, rate pressure product (RPP) and nausea and vomiting score after open-heart surgery. After open heart surgery, 40 patients were randomly allocated to either an Acu-TENS group, which received a 40-min session of TENS applied bilaterally over the acupuncture point PC6 on postoperative days 1–5, or a Placebo-TENS group, which received identical electrode placement but with no electrical output from the TENS unit, despite an output indicator light appearing activated. HR, systolic and diastolic BPs (SBP and DBP) were recorded and RPP computed. Nausea and vomiting symptoms were quantified using a 4-point Likert scale before and after TENS intervention. Daily HR, BP and antiemetic administration data were recorded from a further 20 consecutive subjects who received no intervention and formed the Control group. A trend of decreasing HR and increasing BP in the Acu-TENS group was observed over the five postoperative days, with all variables returning to preoperative values by Day 4 ( P > .2). In the Placebo-TENS and Control groups the HR remained higher ( P < .0001), BP lower ( P < .05) and RPP higher ( P = .01) than respective preoperative values at Day 4. The dose of Maxolon required was lowest in the Acu-TENS group ( P = .038). We concluded that Acu-TENS facilitated an earlier return to preoperative BP, HR and RPP values in patients after acute heart surgery.